2020
DOI: 10.1002/chem.202002489
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Based, Anion‐Doping of Li4Ti5O12 Nanoflowers for Lithium‐Ion Battery Applications

Abstract: This is the author manuscript accepted for publication. It has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…As such, to the best of our knowledge, the work herein presents a thorough investigation, for the first time, of the “triple doping” of LTO using a facile and high-yield hydrothermal method, previously developed by this group. 4 Specifically, as relevant prior studies and justification for our approach, we have previously demonstrated in LTO systems that (a) Ca 2+ can successfully substitute into the Li + site, 13 and separately, that (b) Cl – can be inserted into the O 2– site. 4 As an added level of sophistication, our group improved upon the intrinsic stability of LTO by rational morphological manipulation by either (i) using a micron-scale “flower-like” morphology or (ii) combining LTO with carbon nanotubes.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…As such, to the best of our knowledge, the work herein presents a thorough investigation, for the first time, of the “triple doping” of LTO using a facile and high-yield hydrothermal method, previously developed by this group. 4 Specifically, as relevant prior studies and justification for our approach, we have previously demonstrated in LTO systems that (a) Ca 2+ can successfully substitute into the Li + site, 13 and separately, that (b) Cl – can be inserted into the O 2– site. 4 As an added level of sophistication, our group improved upon the intrinsic stability of LTO by rational morphological manipulation by either (i) using a micron-scale “flower-like” morphology or (ii) combining LTO with carbon nanotubes.…”
Section: Introductionmentioning
confidence: 93%
“… 4 Specifically, as relevant prior studies and justification for our approach, we have previously demonstrated in LTO systems that (a) Ca 2+ can successfully substitute into the Li + site, 13 and separately, that (b) Cl – can be inserted into the O 2– site. 4 As an added level of sophistication, our group improved upon the intrinsic stability of LTO by rational morphological manipulation by either (i) using a micron-scale “flower-like” morphology or (ii) combining LTO with carbon nanotubes. To these LTO motifs, we initiated doping of LTO at the Li site and the O site with Ca 2+ and Cl – , respectively ( Table S2 ).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…So far, numerous strategies have been developed to enhance the ionic‐diffusion property and conductivity of LTO, with the main efforts focused on surface coating/modification/reconstruction, [ 16–18 ] ionic doping, [ 19 ] particle‐size reduction, [ 20 ] and structural design. [ 21,22 ] However, both coating and doping are accompanied by the problems of impurities and side reactions.…”
Section: Introductionmentioning
confidence: 99%